Leaders’ induced justice perceptions as mediator of the relation between participative leadership behaviors and team learning - Raineri, Andres (Frontiers in Psychology, 2023)
In today's complex and rapidly changing business environment, organizations face the need to learn and adapt to emerging challenges and opportunities. Teams have become a preferred vehicle for addressing these challenges, as they bring together diverse perspectives, expertise, and foster collaboration and knowledge sharing among their members. In this context, it is essential for organizations to support team learning by creating an environment conducive to learning within teams. This study draws on Fairness Theory and Social Exchange Theory to explore the role of leader-induced justice perceptions as a mediator in the relationship between participative leadership and team learning. Using a split-half team survey methodology with a sample of 211 work teams, the study examines how team justice climate mediates the relationship between participative leadership behaviors and team learning. The results from structural equation modeling analyses suggest that, at the team level, participative leadership behaviors have both a direct association with team learning and are partially mediated by the team's justice climate. This study contributes to existing literature by providing evidence that leaders' induced justice perceptions play a mediating role in the participatory leadership -team learning relationship. Moreover, the study supports a team level aggregated construct of leader induced justice perceptions. From a practical standpoint, the findings imply that team leaders can contribute to create an environment conducive to team learning by treating team members with fairness.